Comparison of midterm efficacy of Kirschner wires and elastic intramedullary nails after closed reduction of Judet type 3 radial neck fractures in children: a multicenter study - Xu, Zheng; Teng, Jun; Wu, Yuyuan; Xiang, Feng; Xie, Yuyin; Xiang, Junqiao; Liu, Can; Song, Zhenqi; Tang, Zhongwen; Wen, Jie; Li, Yanjun; Xiao, Sheng (Frontiers in Pediatrics, 2024)
Objective: The objective of this study was to compare the midterm efficacy of Kirschner wires and elastic intramedullary nails after the closed reduction treatment of Judet 3 radial neck fractures in children. Methods: This was a retrospective multicenter study of patients diagnosed with Judet type 3 radial neck fractures who underwent closed reduction and internal fixation at four tertiary hospitals from January 2019 to December 2021. Gender, age, fracture type, operation time, follow-up time, X-ray results and complications were collected. The recovery of elbow joint between the two internal fixation methods, elbow motion and complications at the last follow-up were compared. Results: The average operation time of EIN group was statistical significantly increased compared with KW group. There were no significant differences in MEPS score and ROM 3 months after surgery between the two groups, but the ROR Angle of EIN group was statistical significantly increased compared with KW group 3 months after surgery. There were no significant differences in MEPS score, ROM and ROR at the last follow-up. The incidence of complications in EIN group was significantly lower than that in KW group. Conclusion: The use of elastic intramedullary nails fixation or Kirschner wires fixation in the treatment of radial neck fractures in children can both achieve satisfactory fracture reduction and healing. Compared with elastic intramedullary nails, the operation time of Kirschner wires fixation is shorter, and the internal fixation does not need to be removed under anesthesia again, but the complication rate is higher.